The Canadian space agency planetary analogue materials suite. (15th December 2015) - Cloutis, Edward A.; Mann, Paul; Izawa, Matthew R.M.; Applin, Daniel M.; Samson, Claire; Kruzelecky, Roman; Glotch, Timothy D.; Mertzman, Stanley A.; Mertzman, Karen R.; Haltigin, Timothy W.; Fry, Christopher
Abstract: The Canadian Space Agency (CSA) recently commissioned the development of a suite of over fifty well-characterized planetary analogue materials. These materials are terrestrial rocks and minerals that are similar to those known or suspected to occur on the lunar or martian surfaces. These include: Mars analogue sedimentary, hydrothermal, igneous and low-temperature alteration rock suites; lunar analogue basaltic and anorthositic rock suites; and a generic impactite rock suite from a variety of terrestrial impact structures. Representative thin sections of the materials have been characterized by optical microscopy and electron probe microanalysis (EPMA). Reflectance spectra have been collected in the ultraviolet, visible, near-infrared and mid-infrared, covering 0.2–25 μm. Thermal infrared emission spectra were collected from 5 to 50 μm. Raman spectra with 532 nm excitation, and laser-induced fluorescence spectra with 405 nm excitation were also measured. Bulk chemical analysis was carried out using X-ray fluorescence, with Fe valence determined by wet chemistry. Chemical and mineralogical data were collected using a field-portable Terra XRD–XRF instrument similar to CheMin on the MSL Curiosity rover. Laser-induced breakdown spectroscopy (LIBS) data similar to those measured by ChemCam on MSL were collected for powdered samples, cut slab surfaces, and as depth profiles into weathered surfaces where present. Three-dimensional laser camera images of rock textures were collected for selected samples. The CSA intends to make available sample powders (<45 μm and 45–1000 μm grain sizes), thin sections, and bulk rock samples, and all analytical data collected in the initial characterisation study to the broader planetary science community. Aiming to complement existing planetary analogue rock and mineral libraries, the CSA suite represents a new resource for planetary scientists and engineers. We envision many potential applications for these materials in the definition, development and testing of new analytical instruments for use in planetary missions, as well as possible calibration and ground-truthing of remote sensing data sets. These materials may also be useful as reference materials for cross-calibration between different instruments and laboratories. Comparison of the analytical data for selected samples is useful for highlighting the relative strengths, weaknesses and synergies of different analytical techniques. Highlights: A suite of well-characterized lunar and martian analogue materials has been created. A terrestrial impactite sample suite is also included. 16 data types for each sample including mineral, chemical, spectral, and textural.